Association between the comprehensive dietary antioxidant index and adult asthma - Zhizhi Sun; Hanpeng Lai; Rui Sun; Lingfeng Min (Medicine, 2026)
Increasing evidence suggests that oxidative stress plays a key role in the pathogenesis of asthma; however, research on the association of the comprehensive dietary antioxidant index (CDAI) with asthma remains limited. Therefore, this study aims to explore the association between CDAI and asthma. Data from the National Health and Nutrition Examination Survey (NHANES) (2003–2018) were analyzed to examine the association between CDAI, derived from two 24-hour dietary recalls, and asthma, defined by self-reported physician diagnosis. Logistic regression was used to examine the overall association, while restricted cubic spline models were applied to explore potential nonlinear relationships. A total of 35,945 adult participants were included, with 14.2% diagnosed with asthma. In the unadjusted model, higher CDAI levels, particularly within a moderate range, were generally associated with a lower risk of asthma. After adjustment for potential confounders, the highest CDAI quartile showed lower odds of asthma than the lowest quartile; however, this comparison did not reach statistical significance (odds ratio = 0.88, 95% confidence interval: 0.76–1.02; P = .078). Importantly, restricted cubic spline analysis demonstrated a significant nonlinear association between CDAI and asthma ( P for nonlinearity